PERAN DAN PEMIKIRAN TOKOH MASYARAKAT DAN TOKOH AGAMA DALAM MELESTARIKAN HARMONISASI KEAGAMAAN DI KALIMANTAN BARAT - Larsen Wijaya, Diaz Ataya; Parwanto, Wendi (Studia Sosia Religia, 2024)
National stability is an important thing that must be maintained for the sustainability of society livehood. Social diversity often leads to polemics and riots that cause anxiety, but in fact not all diversity leads to hostility. The people of Punggur Kapuas Village place Tomas (community leaders) and Toga (religious leaders) as figures who can lead, adjudicate and maintain the harmony of a plural society. This qualitative research combines field research and library research approaches, and uses the narrative-analytic method to present the findings. Based on the analysis of Peter L. Berger and Thomas Luckmann's reality construct theory on the data obtained in the field, the five religions (Islam, Christianity, Catholicism, Hinduism, and Confucianism) in this village have their own roles in appreciating religious values and transforming them into social understanding. The results of this study are the stages taken in externalization, objectivation and internalization experienced by all elements of the village community. This shows evidence that the role and thoughts of Tomas and Toga have a significant impact in maintaining community interaction and maintaining harmony. This research has implications for the study of religions that show a harmonious village model in social interaction and moderate attitudes applied in community life.